Regional differences in COVID-19 ICU admission rates in the Kingdom of Saudi Arabia: A simulation of the new model of care under vision 2030. Issue 6 (June 2021) - Alharbi, Abdullah A.; Alqassim, Ahmad Y.; Gosadi, Ibrahim M.; Aqeeli, Abdulwahab A.; Muaddi, Mohammed A.; Makeen, Anwar M.; Alhazmi, Abdulaziz H.; Alharbi, Ahmad A.
Abstract: Objective: Saudi Arabia has succeeded in having one of the lowest rates of COVID-19 worldwide due to the government's initiatives in taking swift action to control both the spread and severity of the virus. However, Covid-19 can serve as a test case of the expected response of the new healthcare system under Vision 2030. This study used data from the thirteen present administrative regions of KSA to simulate the variations in ICU admission as a quality indicator in the five business units proposed by a new Model of Care. Methods: We determined the rates of ICU admission for patients with confirmed SARS-CoV-2 (COVID-19) from March to mid-July 2020. The final sample included 1743 inpatients with moderate to severe COVID-19. Patient characteristics, including demographics, pre-existing chronic conditions, and COVID-19 complications, were collected. Business units (BUs) were compared with respect to the relative odds of ICU admission by using multiple logistic regression. Results: After keeping patient and clinical characteristics constant, clear BU differences were observed in the relative odds of ICU admission of COVID-19 patients. Inpatient admission to ICU in our total sample was almost 50%. Compared to the Central BU, the Northern and Western BUs showed significantly higher odds of ICU admission while the Eastern & Southern BUs had significantly lower odds. Conclusion: ICU use for COVID-19 patients differed significantly in KSA healthcare BUs, consistent with variations in care for other non-COVID-19-related conditions. These differences cannot be explained by patient or clinical characteristics, suggesting quality-of-care differences. We believe that privatization and the shift to fewer administrative BUs will help lessen or eliminate altogether the present variations in healthcare service provision.